Peran Relawan Politik Dalam Konstelasi Politik Indonesia - Amalia Syauket (Jurnal Hukum Sasana, 2022)
Direct general elections are the first pillar of democracy in Indonesia, by adhering to a one man, one vote system which requires that anyone who wants a political seat in the government must get the most votes. The presence of volunteers is important for the masses who support one candidate in both the Pilkada and the Presidential Election. The phenomenon of the emergence of this volunteer declaration has begun to emerge, at least we can see it from various reports in the mass media and social media. The presence of political volunteers is a manifestation of the increasing active participation of citizens in substantial democracy. Political volunteers who work offline and online are able to increase community participation which is the key to the presence of an extra-parliamentary democratic government model. By using a qualitative-descriptive approach, the researcher intends to describe the role of political volunteers in the Indonesian political constellation. The results of this study show the phenomenon of political volunteers in the Indonesian Political Constellation as if they have become the main pillars of democratic institutionalization with the way that each moves independently to support their respective candidates so that it can be the starting point of the dynamics of the transformation of political values with patrimonial, oligarchic nuances. towards volunteerism and participation.